Equity and renewable energy: an analysis in residential users in the department of Atlántico-Colombia (2021)
Sustainable development has its complexity in seeking a balance between the three dimensions, renewable energies require an economic investment and are friendly to the environment; but due to socioeconomic differences, access and widespread use may be limited. Colombia has a subsidy mechanism according to socioeconomic strata, where the lower strata receive a reduction in the price of energy by a set amount of kWh, while the upper strata contribute a 20% of the final price. This research performs an economic evaluation due to the investment made in a photovoltaic system, considering socioeconomic factors; The results will make it possible to identify factors that affect equity and access to these technologies.